Gastro-Cardiology: A Novel Perspective for the Gastrocardiac Syndrome - Hofmann, Robin; Bäck, Magnus (Frontiers in Cardiovascular Medicine, 2021)
The gastrocardiac syndrome was coined originally in the beginning of the 19th century to describe an alleged gastric-cardiopathy with reflux heart burn mimicking cardiac chest pain. Today, a wider perspective of the gastrocardiac syndrome has emerged. First, the cardiovascular risk factor chronic systemic inflammation may reflect gastroenterological inflammatory conditions, such as inflammatory bowel disease and gastrointestinal infections, in particular, chronic Helicobacter pylori infection. Second, as contemporary treatment of cardiovascular disease commonly includes potent antithrombotic medications, the cardiovascular benefit in terms of a decrease in the incidence of recurrent ischemic events and death needs to be carefully balanced with an increased risk of gastrointestinal bleeding. Several strategies to target chronic gastrointestinal inflammation and to diagnose and treat Helicobacter pylori to reduce the risk of cardiovascular events and gastrointestinal bleeding are available but residual controversy remains and large-scale gastro-cardiology trials are needed to determine the optimal treatment approaches. In perspective, the centennial gastrocardiac syndrome is more relevant than ever in a contemporary gastroenterology and cardiology setting. A collaborative subspecialty - Gastro-cardiology – would introduce novel unique means to study, diagnose and treat gastrocardiac conditions with the aim to reduce the risk of cardiovascular and bleeding events to improve prognosis for gastro-cardiology patients.